Agronomic performance, postharvest and indirect selection of Coffea arabica L. cultivars for high-temperature regions - Morello, Orlando Ferreira [UNESP]; Checchio Mingotte, Fabio Luiz [UNESP]; Leal, Fabio Tiraboschi [UNESP]; Coelho, Anderson Prates [UNESP]; Neto, Almir Salvador [UNESP]; Lemos, Leandro Borges [UNESP] (Univ Federal Rural Pernambuco, 2020)
This study aim was to evaluate the agronomic performance and the postharvest of small-sized Coffea arabica cultivars and to indicate the best agronomic variable for indirect selecting genotypes for cultivation in high-temperature regions. The experiment was conducted during the 2014/15 harvest, employing the randomized blocks experimental design, with four replicates. The treatments consisted of 17 small-sized coffee cultivars. The evaluated attributes were growth, yield and postharvest of the coffee cultivars. Considering their morphological attributes, the cultivars Obata IAC 1669-20, Catuai Amarelo IAC 62, Obata Amarelo IAC 4739 and IPR 99 were superior to the others. As for yield, the cultivars Obata IAC 1669-20 (51.90 bags ha(-1)), Catuai Amarelo IAC 62 (48.05 bags ha(-1)) and Catuai Vermelho IAC 99 (47.63 bags ha(-1)) were superior. In the post-harvest evaluations, the cultivar Tupi IAC 125 (Tupi RN) had the best results. Due to their better agronomic performance, the cultivars Obata IAC 1669-20 and Catuai Amarelo IAC 62 are thus recommended for high-temperature regions. Plant height tends to be the best agronomic variable for indirect selecting more adapted cultivars for high-temperature regions.
Keywords: adaptation; cultivar competition; plant height; vegetative growth